Padovese, Luigi. II problema della politica nelle prime comunitá cristiane. Casale Monferrato: Piemme, 1998, 265 pp. - Hubeñak, Florencio (2000)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina